STRENGTHENING SMART PORT-BASED PORT GOVERNANCE IN INDONESIA - Bahana Wiradanti; K.P.Suharyono S.Hadiningrat; Fikri Achmad Abdullah (JIPOWER : Journal of Intellectual Power, 2025)
Indonesia's archipelagic geography presents unique challenges in managing a maritime-based nation. The complexity and disparities are particularly challenging and require a greater budget and commitment from the government, stakeholders, and all Indonesian people. The 1957 Djuanda Declaration, ratified by the 1982 UN Convention on the Law of the Sea (UNCHLOS), marked international recognition of Indonesia's status as a large archipelagic nation. However, the utilization of marine resources has not been maximized, necessitating comprehensive, holistic, and integral efforts, including strengthening port governance through smart ports.Smart ports are expected to improve the performance of ports throughout Indonesia, meet international standards, and be highly competitive. Governance must be strengthened in such a way as to achieve good governance, while simultaneously strengthening the quality of human resources and utilizing digital technologies in the maritime sector, such as smart ports.Smart ports, as a port subsystem, have been implemented in various ports worldwide, such as the Port of Rotterdam Authority, Singapore's Maritime and Port Authority (MPA), and the Port of Hamburg, including ports in Indonesia managed by PELINDO.This study employed a qualitative descriptive design with a thematic narrative approach to identify and describe efforts to strengthen smart port-based port governance in Indonesia. Data were collected from various publications from credible official institutions for literature review. The data were then analyzed qualitatively and narrated based on similar themes and comprehensively compared.The data analysis concluded that strengthening smart port-based port governance in Indonesia is being implemented through various efforts, including: strengthening smart port-based port governance has significant potential to improve the efficiency, transparency, and competitiveness of Indonesian ports. Implementation includes strengthening: a) Operational Digitalization; b) Service Optimization: Use of Smart Vision 3D, Berth Monitoring, and Gate & Weighbridge (Weighbridge); c) Data Integration; c) Strengthening Digital Infrastructure; d) Talent Human Resource Development; e) Electrification and Equipment Digitalization; f) Eco-Friendly Terminals.